Neurocognitive profile of the adult population living with type 1 diabetes mellitus: a matched case-control cross-sectional study of metabolism and memory - Meo, Sultan Ayoub; Alotaibi, Metib; Shaikh, Narmeen; Alguwaihes, Abdullah M. (Frontiers in Endocrinology, 2025)
BackgroundDiabetes Mellitus (DM) is a chronic, debilitating condition that causes numerous long-lasting complications. The cognitive health of people with DM is crucial for ensuring holistic development, academic success, and participation in daily life activities. This study aimed to assess the neurocognitive profile and the impact of HbA1c levels and disease duration on the cognitive profile of adults living with type 1 diabetes mellitus (T1DM).MethodsA total of 108 adults (54 T1DM, and 54 controls) were recruited, matched for age, gender, ethnicity, education, and Body Mass Index (BMI). The cognitive functions were measured using the Cambridge Neuropsychological Test Automated Battery (CANTAB). Four different tests were selected to assess the cognitive functions related to executive function, reaction time, visual memory, and spatial working memory in people with T1DM and their matched control group. Further analysis within the diabetic group was conducted based on HbA1c levels, disease duration, and the presence of hypoglycemic symptoms.ResultsThe Attention Switching Task parameters (AST mean correct latency, AST mean correct latency-congruent, AST Mean correct latency-incongruent) show that people with T1DM took significantly longer to respond to the task than the control group (p < 0.001). Moreover, the T1DM group exhibited significantly longer response times in the choice reaction time task (p < 0.001). Additionally, people with T1DM had significantly lower scores in the Pattern Recognition Memory task, suggesting impaired visual memory performance compared to the control group (p < 0.001). Furthermore, the diabetic group made significantly more errors in the spatial working memory task SWM (p<0.001), indicating difficulties in remembering and using spatial information. However, HbA1c levels, disease duration, and the presence or absence of hypoglycemic symptoms in the preceding month among the diabetic group were not associated with measurable differences in any of the cognitive tests.ConclusionCognitive performance was significantly impaired among adults with T1DM. T1DM participants showed slower processing speed, weaker executive functioning, and poorer memory performance compared to well-matched healthy controls. The study’s findings underscore the importance of glycemic management in adults with T1DM. These findings support physicians and policymakers in mitigating cognitive deficits among adults with T1DM.